Weedy and seedy: the rapid evolution of life-history characteristics in an introduced daisy. Issue 5 (18th August 2022) - Brandenburger, Claire R; Maslen, Ben; Sherwin, William B; Moles, Angela T
Abstract: Despite the importance of life-history characteristics in determining a species' success, we still lack basic information about some fundamental life-history elements found across the life cycle of introduced plants. Our study assesses rapid evolutionary divergence in life-history characteristics of the beach daisy Arctotheca populifolia by comparing introduced Australian and source South African plants and measuring eight key variables including seed mass, germination, reproductive output and survival. This is the first study that compares the life history of an introduced plant species with its single original source population, providing a precise and powerful method for detecting evolutionary divergence. We found that introduced A. populifolia has evolved a suite of weedy life-history characteristics in less than 90 years: the introduced plants use a live-fast die-young strategy of germination and survival and produce significantly more inflorescences and more seeds that germinate faster. This knowledge adds to the remarkable data that we already have on the rapid evolutionary divergence occurring in the morphology, physiology and defence of this introduced plant and highlights the speed and scope of evolutionary divergence possible in plants. To fully understand and manage the future of our plant species, we must consider their potential for ongoing change in key aspects of life history. Abstract : Hide How fast could an introduced plant adapt some of its fundamental life-history characteristics to succeed on a new continent an ocean away? We found that in less than 90 years after arriving in Australia, the South African beach daisy has rapidly evolved to become weedier and seedier than its parent population. The introduced Australian plants use a live-fast die-young strategy of germination and survival, and produce significantly more inflorescences and more seeds that germinate faster. In addition, this is the first study that compares the life history of an introduced plant species with its single original source population, providing a precise and powerful method for detecting evolutionary change.